DIVERSIFICATION IN UTILISATION OF OF TRASH FISH BY GAMMA IRRADIATION. - GHADI, S v; MADHAVAN, V N; KUMTA, U S (Fishery Technology, 2017)
Radiation pasteurisation enhances the shelf stability of trashfish varieties and enables the grading of fish depending uponthe freshness quality. As against the ice-chilled fish whichspoils within 8-10 days, exposure to 100 Krad and storage atice temperature helps in maintaining the quality in Grade I,II or III up to 10, 20 or 25 days respectively. The improvementin. quality. thus provides scope fer greater utilisation oftrash fish for variou3 secondary products.